Defect structures in nematic liquid crystal shells of different shapes. Issue 1 (2nd January 2016) - Mirantsev, L. V.; de Oliveira, E. J. L.; de Oliveira, I. N.; Lyra, M. L.
ABSTRACT: The present review is devoted to recent studies of structures with topological defects on nematic liquid crystal (NLC) shells of different shapes and to the possibility of using external electric fields to manipulate these structures. It is shown that principal curvatures of bounding surfaces have a strong effect on the number and arrangement of these defects on NLC shells. It is also shown that external electric fields can be used to control the number of valence centers occurring on these shells, thus unveiling their capability of acting as multivalent building blocks for nanophotonic devices.